Intimate partner violence in Germany before and during the COVID-19 pandemic: A gender perspective - Haverkamp Rita; Hohendorf Ines (Temida, 2023)
The article discusses intimate partner violence (IPV) before and during the COVID-19 pandemic, focusing on the extent to which victimization has changed. International studies on IPV have attributed victimization to the social character of the sexes, with an explicit analysis of gender attitudes, beliefs and gender roles. Consistent with this international approach, the gender attitudes of individuals are used to examine the link between social character and victimization. The study draws on a sample of mainly young adults as the empirical basis for a quantitative analysis conducted at a German University in the spring of 2021. The article explores the extent to which gender stereotypes occur, their impact on the likelihood of victimization and how the COVID-19 pandemic has affected IPV and role models.